2000
DOI: 10.1901/jaba.2000.33-167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous and Intermittent Reinforcement for Problem Behavior During Functional Communication Training

Abstract: We evaluated the effectiveness of functional communication training (FCT) in reducing problem behavior and in strengthening alternative behavior when FCT was implemented without extinction. Following the completion of functional analyses in which socialpositive reinforcement was identified as the maintaining variable for 5 participants' selfinjurious behavior (SIB) and aggression, the participants were first exposed to FCT in which both problem behavior and alternative behavior were reinforced continuously (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 12 publications
5
74
1
1
Order By: Relevance
“…The Phase 1 and Phase 2 functional analyses for Janet, Mary, and Shelby were separated by treatment conditions not reported in this study (all other functional analyses were conducted back to back). Figure 1 shows results of the functional analyses for Bob, Annette, Jed, and Max (note that portions of the data for Annette, Jed, and Max also appear in Worsdell, Iwata, Hanley, Thompson, & Kahng, 2000). Bob's data in Phase 1 showed that his highest rates of SIB occurred in the attention condition.…”
Section: Experimental Designmentioning
confidence: 99%
“…The Phase 1 and Phase 2 functional analyses for Janet, Mary, and Shelby were separated by treatment conditions not reported in this study (all other functional analyses were conducted back to back). Figure 1 shows results of the functional analyses for Bob, Annette, Jed, and Max (note that portions of the data for Annette, Jed, and Max also appear in Worsdell, Iwata, Hanley, Thompson, & Kahng, 2000). Bob's data in Phase 1 showed that his highest rates of SIB occurred in the attention condition.…”
Section: Experimental Designmentioning
confidence: 99%
“…This includes individuals in preschool (e.g., Durand 1993;Durand and Carr 1987;Gibson et al 2010;Mancil et al 2009;Wacker et al 2013), elementary school (e.g., Durand and Carr 1991;Franco et al 2009;, secondary school (e.g., Carr and Durand 1985;Fisher et al 2005), and adults (e.g., Kahng et al 1997;*Shirley et al 1997;*Worsdell, A. S et al 2000).…”
mentioning
confidence: 99%
“…Undetected differences between programmed and obtained rates of reinforcement could potentially introduce unexpected variability in the data or unexplained effects. For example, the findings of a number of applied studies suggest that when concurrent FR 1 FR 1 reinforcement schedules are arranged, problem behavior is more likely to occur than an appropriate alternative response (DeLeon, Fisher, Herman, & Crosland, 2000;Shirley, Iwa-ta, Kahng, Mazaleski, & Lerman, 1997;Worsdell, Iwata, Hanley, Thompson, & Kahng, 2000). This apparent response bias might be accounted for by reinforcement history (DeLeon et al, 2000).…”
mentioning
confidence: 99%